ABSTRACT Wastewater Treatment Plant (WWTP) with aerobic processes is required to reduce high organic components of date juice wastewater. Characterization, optimization of operating condition as well as alternative operation of WWTP are required in the process development wastewater treatment, so the output of wastewater that satisfies the environmental quality standards. This study aims to characterize of the WWTP unit's operating conditions, determine of lime dose, optimize aeration time - Eko Sawirfi Suprihatin dan Ono Suparno (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT Wastewater Treatment Plant (WWTP) with aerobic processes is required to reduce high organic components of date juice wastewater. Characterization, optimization of operating condition as well as alternative operation of WWTP are required in the process development wastewater treatment, so the output of wastewater that satisfies the environmental quality standards. This study aims to characterize of the WWTP unit's operating conditions, determine of lime dose, optimize aeration time, and identife of the alternative treatment. Characterization of the wastewater indicated that all units did not have an optimum operating condition. Characteristics output of the wastewater were COD of 2,344 mg/L, TSS of 135 mg/L, pH of 5.5, and turbidity of 182 FTU, the values did not meet the quality standards. The improvement a dose of lime neutralization at pH 7 is 0.6 g/L. Condition of 24-hour aeration time demonstrated effluent quality: COD of 351 mg/L, TSS of 78 mg/L, pH of 6.3, and turbidity of 92 FTU, which are better than those of aeration time 12 until 20 hours. The high content of COD could be overcome by an anaerobic treatment. Identification of an anaerobic treatment system could potentially produce biogas with yield of 26.46 m3/day.                                                                                                               Key words : wastewater, wastewater treatment plant, anaerobic, environmental quality standards